2019
DOI: 10.1080/21711976.2019.1644003
|View full text |Cite
|
Sign up to set email alerts
|

Interest of Social Representations Theory to grasp coastal vulnerability and to enhance coastal risk management (Interés de la Teoría de las Representaciones Sociales para entender la vulnerabilidad costera y para mejorar la gestión de los riesgos costeros)

Abstract: This theoretical paper provides a new perspective on coastal vulnerability analysis by combining geography and psycho-social approaches. Most studies on perceptions of coastal risks report that people who are exposed have a low level of perceived vulnerability (they are not anxious), strong place attachment (they love their living place and want to live close to the sea) and are resistant to changes in adaptation strategies (they do not want to move away). For natural scientists and managers, these findings us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…For example, people who have lived their whole life in Port-Saint-Louis-du-Rhône (PSLR) are able to describe exactly what the meteorological conditions should be for the Rhône river to attain its maximum level. Simultaneous high risk awareness and deep place attachment has been described as a paradox (Meur-Ferec & Guillou, 2020). Our comparative study between two communities with different coastal risk cultures (PSLR and Fréjus) found that PSLR inhabitants, who share a strong place attachment, also demonstrate a deep understanding of how their environment works and how dangerous it can be (Bertoldo et al, this issue).…”
Section: Local History and Trustmentioning
confidence: 87%
“…For example, people who have lived their whole life in Port-Saint-Louis-du-Rhône (PSLR) are able to describe exactly what the meteorological conditions should be for the Rhône river to attain its maximum level. Simultaneous high risk awareness and deep place attachment has been described as a paradox (Meur-Ferec & Guillou, 2020). Our comparative study between two communities with different coastal risk cultures (PSLR and Fréjus) found that PSLR inhabitants, who share a strong place attachment, also demonstrate a deep understanding of how their environment works and how dangerous it can be (Bertoldo et al, this issue).…”
Section: Local History and Trustmentioning
confidence: 87%
“…On the other hand, this content also shows a negative association between place attachment and risk perception when local risk knowledge contributes to reinforcing feelings of control and self-sufficiency -'here, we know'described as an attenuating factor for risk perception and preparedness (Luís et al, 2016). In the following section we will illustrate how discourse about local risks can help resolve the paradox between local place attachment and risk perception (Meur-Ferec & Guillou, 2020).…”
Section: Emotional Ties To the Coastmentioning
confidence: 95%
“…Studies have demonstrated that along the French Atlantic (Michel-Guillou, Lalanne, & Krien, 2015;Michel-Guillou & Meur-Ferec, 2017) and Mediterranean (Durand et al, 2018) coasts local inhabitants are aware of their exposure to coastal flooding yet unworried by the risk (Meur-Ferec & Guillou, 2020;Michel-Guillou et al, 2016;Michel-Guillou et al, 2015). This has been described, from a strictly informational perspective, as a "poor risk culture" (Durand et al, 2018. p. 10).…”
Section: Living With Long 'Known' Risks: Social Representations and Coastal Risksmentioning
confidence: 99%
See 2 more Smart Citations